2007
DOI: 10.3989/gya.2007.v58.i4.449
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid and cholesterol composition of enriched egg yolk lipids obtained by modifying hens’ diets with fish oil and flaxseed

Abstract: RESUMENComposición en ácidos grasos y colesterol de los lí-pidos de yema de huevo enriquecida mediante modificación de la dieta de gallinas con aceite de pescado y linaza.Se han estudiado los efectos producidos por la presencia de aceite de pescado y linaza, en la dieta de gallinas ponedoras, sobre la composición en colesterol y ácidos grasos de los lípidos del huevo. Se han utilizado gallinas ponedoras Isa-White y cinco tipos de dietas experimentales. La primera dieta fue usada como control. Se añadió aceite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
2
8
0
1
Order By: Relevance
“…The present study showed that there was significant decrease in the n6: n3 ratio from T 1 to T 7 . In agreement with present findings, Aymond and Elswyk, (1995), Ansari et al, (2006), Goncuglu and Ergun (2004), Van Elswyk (1997), Yalcyn et al, (2007), Galobart et al, (2001),. Grobas et al, (2001), Shapira et al, (2008), Souza et al, (2008), T. Sujatha and D. Narahari (2011), Kirubakaran A. et al, (2011), Oliveira et al, (2010 and Omar et al, (2014) reported that linseed oil supplementation in ration of layer increases PUFA and decreases n6:n3.…”
Section: Fatty Acid Profilesupporting
confidence: 82%
“…The present study showed that there was significant decrease in the n6: n3 ratio from T 1 to T 7 . In agreement with present findings, Aymond and Elswyk, (1995), Ansari et al, (2006), Goncuglu and Ergun (2004), Van Elswyk (1997), Yalcyn et al, (2007), Galobart et al, (2001),. Grobas et al, (2001), Shapira et al, (2008), Souza et al, (2008), T. Sujatha and D. Narahari (2011), Kirubakaran A. et al, (2011), Oliveira et al, (2010 and Omar et al, (2014) reported that linseed oil supplementation in ration of layer increases PUFA and decreases n6:n3.…”
Section: Fatty Acid Profilesupporting
confidence: 82%
“…There is a strong relationship between the cholesterol profile of egg and the plasma cholesterol level [1]. Nutritionists have agreed that dietary polysaturated fatty acids (PUFA) of n-3 series play a crucial role in human health by promoting growth and development and demonstrate antithrombotic and antilipidemic effects [2][3][4]. The fatty acid composition of the egg may be influenced by the dietary composition offered to the laying hens [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, this dish often also contain red meat and offals as constituents with a high dietary cholesterol content and which may be responsible for the high cholesterol content of this dish. Yam with eggs also had a high concentration of cholesterol; this amount is not surprising because many studies (Oloyede, ; Yalcyn et al ., ; Spence et al ., ) have implicated a high concentration of cholesterol in egg yolk. Aside from the aforementioned dishes, most of the traditional dishes analysed in the present study had low to marginal concentrations of dietary cholesterol; this is in consonance with many scientific studies indicating that traditional diets tend to have lower amounts of dietary cholesterol compared to dishes of western origin.…”
Section: Discussionmentioning
confidence: 99%